Evaluating the efficacy of Masters coursework criteria sheets using a 10 question framework. Issue 3 (16th March 2019) - Grainger, Peter; Heck, Deborah; Christie, Michael
Abstract: This paper builds on an earlier study that developed a 10 question framework for improving the quality of criteria sheets (also known as rubrics) used in Master of Education programmes. To test that framework 15 rubrics were independently evaluated by seven teachers using the above mentioned framework. Raw data from the evaluations were collated and coded and then further analysed in three sequential, substantive conversation sessions, in order to investigate the inter-connectedness of three assessment concepts, namely, grading, moderation and feedback. The study revealed that the key to criteria sheet effectiveness is the explicitness of the standards descriptors. The research also identified three broad questions that can help teachers evaluate the quality of their criteria sheets. These questions focus on the clarity of the task description and ways of improving the criteria and standards by which student responses are to be judged. The revised questions provide an effective framework for assuring the quality of these three aspects of assessment within units (also known as courses) in postgraduate programmes.